The Effectiveness of Parent-Child Play Therapy with Parent Behavioral Management Training on Reducing Externalizing Problems and Shyness - Ghazavi, Seid Habibollah; Arab, Ali (Applied Family Therapy Journal (AFTJ), 2021)
Aim: The aim of this research was determine the effectiveness of parent-child play therapy with parent behavioral management training on reducing externalizing problems and shyness in fourth grade male students. Methods: This study was semi-experimental with a pretest-posttest design with a control group. The research population was fourth grade male students of Khour Va Biabanak County in 2019-20 academic years. Number of 40 student were selected by available sampling method and randomly replaced into two equal groups. The experimental group underwent 10 sessions of 60-minutes the intervention of parent-child play therapy with parent behavioral management training and during this period the control group didn’t receive any training. Data were collected by externalizing problems subscale in Achenbach child behavior checklist (1991) and Stanford shyness scale (1977). Data analysis was performed using multivariate repeated-measures analysis of variance. Result: The results showed that the parent-child play therapy with parent behavioral management training led to reducing externalizing problems (F=52.15, P<0.001) and shyness (F=39.81, P<0.001) in fourth grade male students, and the impact was stable at the follow-up stage (P=0.05). Conclusion: The results indicated the effectiveness of parent-child play therapy with parent behavioral management training on reducing externalizing problems and shyness of male students and it can be used along with other effective treatment methods for psychological interventions, especially to reduce externalizing problems and shyness.